Public relations' disruption model on chatgpt issue - Kertati, Indra; Sanchez, Carlos Y.T.; Basri, Muhammad; Husain, Muhammad Najib; Winoto Tj, Hery (Jurnal Studi Komunikasi, 2023)
With the rising of AI technology, a new disruption occurred in society. Disruption can actually be a social phenomenon that exists even in Indonesian society. However, the current state is making the disruption become a commercial interest. A bold example is Tesla's AI Bot named Optimus in the @TeslaAIBot account and a new GPT used for Twitter commentaries called @ReplyGPT. Content Analysis was the methodology for this research, with crawling data related to ChatGPT from Twitter from December 2022-January 2023. Both served as the bridge between humans and AI, and both pushed awareness that there are other creatures than humans. The sequential explanatory design method will discover a new perspective of GPT as advanced technology. People realise that the closest thing that could change human civilisation is language models.